A design method for the prediction of load distribution in hollow-core floors. (15th September 2016) - Bernardi, P.; Cerioni, R.; Leurini, F.; Michelini, E.
Highlights: Load distribution in hollow-core floors is modelled through a general approach. Model schematizes floor units as Saint-Venant beams and joints as rotational hinges. The solving system is expressed only as a function of the shear forces in joints. Obtained results are in good agreement with experimental data from the literature. Model is applied to construction of design charts to be used in current practice. Abstract: A general design method is provided to predict the load distribution at serviceability condition in hollow-core floors formed by precast units linked together through cast in place reinforced concrete joints. Each panel forming the floor is schematized as a Saint-Venant beam connected to the others by means of rotational hinges. In this way, the only unknowns of the solving system, characterized by an exponential dichotomy, are represented by shear forces transmitted along joints. The model is first validated through comparisons with significant experimental results available in the literature, and subsequently applied to the construction of design charts to be used in current practice. These latter are also compared with the provisions on load distribution effects suggested by European Standard UNI EN 1168, pointing out some limitations of current design procedures and suggesting possible improvements.